(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3eOjfI MeU s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg jbGd bjS Hf GdMGQK gh GdMGQK Hf cdOI GdKbai GdWjH ehdi CHj HcQ s
(3BNQgG (B:s
(3LeYfG Gddg hEjGce eYTQ GdENhGf Ydi WGYJg hCMdfG hEjGce OGQ cQGeJg eY eMeO GdeUWai hBdg hUMGHJg s
(3bhHdJ Ydi fSNI bQFJ Ydi GdeDdas
(3fbdJ ef fSNI cJHJ SfI (B637(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GdMOjK h GdeUWdMs